Effect and impression of structured feedback in formative assessment of medical undergraduates of Eastern India - Sanghamitra Chakraborty; Sunita Vagha; Sebanti Chakrabarty (Wolters Kluwer Medknow Publications, 2024)
Feedback, the integral component of formative assessment, should be timely, specific, and methodical. Feedback is a stop-gap that helps the learner to assess their performance and reinforce their desire to learn. This study was conducted to explore the effectiveness of feedback in improving the performance of medical undergraduates in formative assessment and assessment of perceptions of students about feedback. This comparative interventional study was conducted to monitor the improvement in formative assessment scores after the structured feedback. Medical undergraduates of phase1 (Bachelor of Medicine and Bachelor of Surgery (MBBS) Batch 2022-2023) of Bankura Sammilani Medical College and Hospital were included as the study participants. The proportion of students having scores <50% and >50% between the two formative assessments were compared using the Chi-square test. A questionnaire in the Likert scale was devised to assess the perception of students regarding quality of feedback and analyzed by Tastle and Wierman formula. The number of students scoring > 50% as well as their mean formative assessment scores increased significantly after feedback (P = 0.0009). The majority of the students proclaimed that feedback was non-judgmental and motivated for the study. Feedback motivated students to assess their deficits and encouraged the desire to study to overcome the lacunae. The majority of the students (65.9%) strongly voiced that the feedback was effective, valuable, and non-judgmental.